Confronting the Digital Divide: Debunking Brave New World Discourses. (20th May 2017) - Rowsell, Jennifer; Morrell, Ernest; Alvermann, Donna E.
Abstract: There is far more to the digital divide than meets the eye. In this article, the authors consolidate existing research on the digital divide to offer some tangible ways for educators to bridge the gap between the haves and have‐nots, or the cans and cannots. Drawing on Aldous Huxley's notion of a "brave new world, " some digital divide approaches and frameworks require debunking and are strongly associated with first‐world nations that fail to account for the differential access to technologies that people who live in poverty have. Taking a closer look at current realities, the authors send out a call to teachers, administrators, and researchers to think more seriously and consequentially about the effect the widespread adoption of technologies has had on younger generations and the role of the digital on knowledge creation and on imagined futures.